2019
DOI: 10.3390/ijerph16214061
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Physical Activity Performed by Young Adults

Abstract: Despite the World Health Organization considering it important to promote physical activity as part of a healthy lifestyle, the official data show an increase in the percentage of physical inactivity, which has brought about the development of strategies at different levels (national and international) to reverse this trend. For the development of these strategies, it is relevant to know what the determinants of physical activity (at leisure and at work) are. Therefore, this is going to be analysed in the auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
2
14
0
2
Order By: Relevance
“…There are some differences between men and women aged 30–44 in terms of the relationship with loneliness when living with a partner, but it is not significant ( p < 0.0027). These data are related to the findings in the city of Seville, Spain [ 16 ]. In the group aged 15 to 29, 26.66% of men and 17.77% of women perform physical exercise, but these figures do not persist into adulthood.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…There are some differences between men and women aged 30–44 in terms of the relationship with loneliness when living with a partner, but it is not significant ( p < 0.0027). These data are related to the findings in the city of Seville, Spain [ 16 ]. In the group aged 15 to 29, 26.66% of men and 17.77% of women perform physical exercise, but these figures do not persist into adulthood.…”
Section: Discussionsupporting
confidence: 85%
“…In the group aged 15 to 29, 26.66% of men and 17.77% of women perform physical exercise, but these figures do not persist into adulthood. A study found a significant inverse correlation between the level of education and physical exercise at work from 24 to 44 years old [ 16 ]. Another study provides significant results in terms of age, sex, relationship with labor resources and physical demands, and academic years in a population aged 50–70 years old [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, targeting family and peers in promoting active lifestyles should be considered with caution. The actual evidence suggests that social support positively affects the PA, although the association is still unclear and supported by mixed evidence [ 121 , 122 , 123 , 124 , 125 ]. Community interventions should take into consideration the whole and complex choice architecture of individuals, considering both the individual’s family and the specific cultural and social contexts and dynamics [ 57 , 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, poucas informações sociodemográfi cas, do estilo e da qualidade de vida estão disponíveis acerca dos participantes de programas públicos de atividade física no Brasil, especialmente, na região nordeste 11 . Este conjunto de conhecimentos é importante para prover melhoria contínua das ações de promoção da saúde 11,[13][14][15][16][17] , adequandose às necessidades do público-alvo. Portanto, os objetivos dessa pesquisa foram: i) descrever características sociodemográfi cas, do estilo de vida e de doenças crônicas de iniciantes no projeto JPVS; e ii) descrever a qualidade de vida dos participantes após um ano de intervenção pelo projeto JPVS.…”
Section: Nounclassified